1988
DOI: 10.1111/j.1474-919x.1988.tb02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Vocal mimicry of hosts by Great Spotted Cuckoo Clamator glandarius: further evidence

Abstract: Great Spotted Cuckoo nestlings were shown, after some days in the nest, to have begging calls that differed depending on whether they were being reared by Magpies or Carrion Crows. They also produced calls of a pitch and repetition rate that implied a high level of hunger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…Previous studies of the begging displays of Great Spotted Cuckoos claimed that nestling Cuckoos mimic the begging calls of host young (Mundy , Redondo & Arias de Reyna ). Both previous studies had extremely low sample sizes (one Cuckoo chick in Mundy and similarly limited sample sizes in Redondo & Arias de Reyna , T. Redondo pers. comm.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of the begging displays of Great Spotted Cuckoos claimed that nestling Cuckoos mimic the begging calls of host young (Mundy , Redondo & Arias de Reyna ). Both previous studies had extremely low sample sizes (one Cuckoo chick in Mundy and similarly limited sample sizes in Redondo & Arias de Reyna , T. Redondo pers. comm.)…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that Great Spotted Cuckoo nestlings mimic the begging call of chicks of the Pied Crow Corvus albus (its main host in South Africa, where the study was carried out). Later, Redondo and Arias de Reyna () reported that nestlings from naturally parasitized nests of its two main hosts in Europe (Eurasian Magpie and Carrion Crow) produced different begging calls resembling host nestling calls. Therefore, these two previous studies indicated differences in begging calls of Great Spotted Cuckoo nestlings when parasitizing different host species (resembling the begging calls of each host species).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several generalist cuckoo species possess begging call polymorphisms (e.g., Diederik cuckoo C. caprius , Reed 1968; Long‐tailed koel Eudynamys taitensis , McLean and Waas 1987; Great‐spotted cuckoo Clamator glandarius , Redondo and Arias‐de‐Reyna 1988; Horsfield's bronze‐cuckoo Chalcites basalis , Payne and Payne 1998), each morph resembling the nestling begging call of a different host species and apparently indicating the existence of host‐specific races. Mimetic begging calls may have evolved as a result of selection on cuckoo nestlings to tune into existing channels of offspring–parent communication and thereby elicit optimal parental provisioning (e.g., Davies et al 1998; Kilner et al 1999) or to evade recognition and rejection by hosts (Langmore et al 2003), but it is not known whether they are innately encoded or acquired after parasitism.…”
mentioning
confidence: 99%
“…Many parasitic cuckoo nestlings are virtuosos at mimicking the vocal calls of host nestlings, which, like egg mimicry, presumably ensures the cuckoo nestling is accepted and cared for by host parents (e.g. McLean & Waas 1987;Redondo & Arias de Reyna 1988;Langmore et al 2003). Having been accepted, parasitic nestlings then often exaggerate those features of the host nestling's begging displays that are critical to attracting parental care, such as amplitude and call rate (Redondo 1993;Davies et al 1998;Kilner et al 1999).…”
Section: Introductionmentioning
confidence: 99%